Humanitarian Logistics and the Problem of Floods in a Smart City - Bastarrachea-Almodovar, Aztlán; Estrada Barbosa, Quirino; Reynoso Jardón, elva; Molina Salazar, Javier (Taylor & Francis, 2021)
Floods are natural disasters resulting from various factors, such as poor urban planning, deforestation and climate change, to provide just a couple of examples. The consequences of such disasters are often devastating and bring with them not only losses of millions of dollars but also of human lives. The purpose of this work is to offer a first approximation of people’s reactions in the case of an evacuation due to a hypothetical flood in an area located in the Colonia Bellavista of Ciudad Juárez that is adjacent to the Río Bravo, the Acequia Madre, and the Díaz Ordaz viaduct, which are plausible to be subject to overflow or flooding after heavy torrential rains in a scenario where climate change has seriously affected the city's climate.